Democracy, Human Development, and Economic Growth: A Panel Data Approach - Hamdani, Imam (Formosa Journal of Multidisciplinary Research, 2024)
Sustainable economic growth is the primary goal of development in Indonesia, but it cannot be separated from the role of democracy and human development. This study aims to analyze the impact of the Indonesian Democracy Index (IDI) and the Human Development Index (HDI) on economic growth in Indonesia from 2015 to 2023. The method used is panel data regression with the Random Effect Model (REM) applied to panel data from 34 provinces in Indonesia. The results show that both IDI and HDI have a positive and significant impact on economic growth, both simultaneously and partially. The IDI coefficient of 2538.056 with a t-statistic probability of 0.0013 indicates that increasing IDI can enhance economic growth. Meanwhile, HDI has a coefficient of 18923.955 with a t-statistic probability of 0.0000, demonstrating the importance of education, healthcare, and living standards in supporting labor productivity and economic growth. The coefficient of determination (R²) is 28.52%, indicating that other factors, such as infrastructure, fiscal policies, and institutional aspects, influence economic growth by 71.48%. This study concludes that improvements in IDI and HDI are crucial factors in promoting equitable and sustainable economic growth in Indonesia. Therefore, policies that strengthen democracy and improve the quality of human development should be prioritized in national development strategies.